Pelaksanaan Reklamasi Lahan Pasca Tambang PT Rekasindo Guriang Tandang di Bengkulu - Rokky Gumanti; Pico Pudiansa; Melian, Muhammad; Reflis, Reflis; Satria P Utama (Yayasan Literasi Sains Indonesia, 2024)
Coal mining in Indonesia is generally carried out using open pit mining methods, thereby disrupting and destroying the ecosystem and natural balance, causing negative impacts that result in environmental damage. Therefore, sustainable development with an environmental perspective is important for every nation and country that wants to protect its natural resources. The main cause of damage to the ecosystem or environment is humans. This research was conducted using a qualitative approach method. According to Williams (1988), the qualitative method is an approach that in the research proposal, process, hypothesis, going into the field, data analysis and data conclusions up to writing uses aspects of trends, non-numerical calculations, situational descriptive, interviews, in-depth analysis, deep. contents, snowballs and stories. The research findings regarding the study of the implementation of ex-mining land reclamation at PT Rekasindo Guriang Tandang's Coal Mining Business License in North Bengkulu Regency, Bengkulu Province are regarding community knowledge and participation in reclamation activities, land preparation, implementation of activities, equipment, costs, and commitment of directors or managers. The implementation of reclamation activities at PT Rekasindo Guriang Tandang did not go well because the plant growth success rate was low and plant growth was less than optimal. So the government and Mining Business License (IUP) managers need to take policies to involve the community more to play a more active role in reclamation activities carried out in areas around their environment.